Program Bina Desa Pengembangan Peternakan Kambing di Kelurahan Anggoeya Kecamatan Poasia Kota Kendari - Rusdin, Muh.; Malesi, La; Zulkarnain, Deki; Aku, Achmad Selamet; Indi, Amiluddin; Sani, La Ode Arsad; Pagala, Muh. Amrullah; Nafiu, La Ode; Hafid, Harapin; Kemistri, Asma Bio; Prasanjaya, Putu Nara Kusuma; Surahmanto; Nurhayu; Asminaya, Nur Santy (CV. Literasi Indonesia, 2023)
This village development program aims to increase the knowledge and skills of breeders in optimizing the utilization of the economic potential of goat livestock production in the Anggoeya Village, Poasia District, Kendari City. The implementation of the village development program uses a participatory method through several stages of activity, namely program socialization and FGD, demonstration of forage planting plots for livestock, feed processing, and composting using goat manure. The results of the implementation of the village development program show that goat breeders are very enthusiastic about participating in all stages of the activity and can feel the benefits of this community service program in the form of additional goat husbandry knowledge and technology. Goat farmers now have forage gardens using quality Odot grass seeds as a solution for providing the sustainable feed. In addition, goat breeders can provide goat feed by making silage using agricultural waste such as banana cobs and straw from other plants. Goat farmers can also produce compost using good quality goat manure which is useful for fertilizing forage crops, developed and or sold as a supplement to their income.